Survival After Rate-Responsive Programming in Patients With Cardiac Resynchronization Therapy-Defibrillator Implants Is Associated With a Novel Parameter: The Heart Rate Score. (August 2016) - Olshansky, Brian; Richards, Mark; Sharma, Arjun; Wold, Nicholas; Jones, Paul; Perschbacher, David; Wilkoff, Bruce L.
Abstract : Background—: Rate-responsive pacing (DDDR) versus nonrate-responsive pacing (DDD) has shown no survival benefit for patients undergoing cardiac resynchronization therapy defibrillator (CRT-D) implants. The heart rate score (HRSc), an indicator of heart rate variation, may predict survival. We hypothesized that high-risk HRSc CRT-D patients will have improved survival with DDDR versus DDD alone. Methods and Results—: All CRT-D patients in LATITUDE remote monitoring (2006–2011), programmed DDD, had HRSc calculated at first data upload after implant (median 1.4 months). Patients subsequently reprogrammed to DDDR 7.6 median months later were compared with a propensity-matched DDD group and followed for 21.4 median months by remote monitoring. Data were adjusted for age, sex, lower rate limit, percent atrial pacing, percent biventricular pacing, and implant year. The social security death index was used to identify deaths. Remote monitoring provided programming and histogram data. DDDR programming in CRT-D patients was associated with improved survival (adjusted hazard ratio =0.77; P <0.001). However, only those with baseline HRSc ≥70% (2308/6164) had improved HRSc with DDDR (from 88±9% to 78±15%; P <0.001) and improved survival (hazard ratio =0.74; P <0.001). Patients with a high baseline HRSc and significant improvement over time were more likely to survive (hazard ratio =0.63; P =0.006). For patients with HRSc <70%, DDDR reprogramming increased the HRSc from 46±11% to 50±15% ( P <0.001); survival did not change. The HRSc did not change with DDD pacing over time. Conclusions—: In CRT-D patients with HRSc ≥70%, DDDR reprogramming improved the HRSc and was associated with survival. Patients with lower HRSc had no change in survival with DDDR programming.